1975
DOI: 10.1002/1097-0142(197510)36:4<1348::aid-cncr2820360424>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for origin of certain childhood acute lymphoblastic leukemias and lymphomas in thymus-derived lymphocytes

Abstract: Lymphoblasts from children with acute lymphoblastic leukemia (ALL) or malignant lymphoblastic lymphoma were studied using surface markers characteristic of T and B lymphocytes. A Bcell marker, i.e. surface immunoglobulin, was absent in all cases studied. Fourteen of 22 children (64%) had lymphoblasts with one or both markers of T lymphocytes, i.e. receptors for sheep erythrocytes (E) and/or human T-lymphocyte antigen (HTLA) detectable using heterologous antithymocyte sera abmrbed with B lymphocytes. In all ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The cells, whether in the marrow or elsewhere, are of lymphoblasts with E receptors (Borella and Sen, 1973;Smith et al, 1973;Catovsky et al, 1974a;Kaplan et al, 1974;Ritter et al, 1975;Stein et al, 1976) and/or human T-lymphocyte antigen (Kersey et al, 1975;Greaves, 1977). The finding in some cases of complement receptors in addition to the E receptor has been interpreted as an indication that the cells derive from immature T-precursor cells (Stein et al, 1976).…”
Section: Morphology Of Lymphatic Cells and Of Their Derived Tumoursmentioning
confidence: 99%
“…The cells, whether in the marrow or elsewhere, are of lymphoblasts with E receptors (Borella and Sen, 1973;Smith et al, 1973;Catovsky et al, 1974a;Kaplan et al, 1974;Ritter et al, 1975;Stein et al, 1976) and/or human T-lymphocyte antigen (Kersey et al, 1975;Greaves, 1977). The finding in some cases of complement receptors in addition to the E receptor has been interpreted as an indication that the cells derive from immature T-precursor cells (Stein et al, 1976).…”
Section: Morphology Of Lymphatic Cells and Of Their Derived Tumoursmentioning
confidence: 99%
“…Such studies have indicated that chronic lymphocytic leukaemia (Pernis et al, 1971 ;Aisenberg & Bloch, 1972;Preud'homme & Seligmann, 1972;Moller, 1973;Kersey et al, 1978) and the majority of malignant lymphomas in adults (Leech et al, 1975;Gajl-Peczalska et al, 1975;Aisenberg & Long, 1975;Lukes et al, 1978;Kersey et al, 1978) appear to represent instances of clonal proliferations of B lymphocytes. In most childhood acute lymphocytic leukaemias the abnormal cells either show characteristics of T lymphocytes (Lukes & Collins, 1974;Stein et al, 1976;Catovsky & Galton, 1976) or lack conventional markers to identify them as either T or B lymphocytes or monocytes (Brouet et al, 1975;Kersey et al, 1975;Sen & Borella, 1975). It has also become increasingly evident that true histiocytic lymphomas are uncommon (Aisenberg & Long, 1975;Gajl-Peczalska et al, 1975;Lukes et al, 1978;Siegal et a/., 1978).…”
mentioning
confidence: 99%
“…At present no one questions the existence of two distinct types of ALL: T-ALL and O-ALL, according to widely accepted immunological criteria [5,7,9,13]. T-ALL is classified by a membrane antigen which is supposed to be specific for T-lymphocytes and their precursors.…”
mentioning
confidence: 99%
“…The ability of these cells to form non-immune rosettes with SRBC is taken as an additional proof, but not as absolute presupposition for their T-cell nature. It has been shown that lymphoblasts of some T-ALL cases express both T-lymphocyte specific markers-receptors for SRBC and T-membrane antigen-whereas cells from other T-ALL cases carry only T-antigen [9,13,20]. Cases of ALL lacking all T-and B-cell markers were classified as "O"-ALL [5,7,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation